1967
DOI: 10.3758/bf03330747
|View full text |Cite
|
Sign up to set email alerts
|

Effects of septal stimulation in rats on heart rate and galvanic skin response

Abstract: Effects of septal stimulation in rats on heart rate and galvanic skin response J Stimulation of the septal area of the brain resulted in pronounced heart rate deceleration and little or no galvanic skin response. The sudomotor findings were interpreted as an indication that heart rate slowing was chiefly due to sympathetic inhibition. Fibers of the fornix seem to be involved in the inhibitory process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

1969
1969
2000
2000

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…It is known, for example, that septal lesions impair inhibitory responses to punishment, delay the extinction of responding when reinforcers are removed, and increase response rates under differential reinforcement of low rate schedules (Grossman, 1977;Gray & McNaughton, 1983). Furthermore, there are similarities between the behavioural and physiological effects of septal lesions and stress exposure such as increased irritability, resistance to extinction and sympathetic activation (Holdstock, 1967;Chen & Amsel, 1977;Feldon & Gray, 1979;Gray, 1987). Thus, we predicted that septal inactivation might mimic the effect of footshock stress on reinstatement of heroin seeking.…”
Section: Introductionmentioning
confidence: 99%
“…It is known, for example, that septal lesions impair inhibitory responses to punishment, delay the extinction of responding when reinforcers are removed, and increase response rates under differential reinforcement of low rate schedules (Grossman, 1977;Gray & McNaughton, 1983). Furthermore, there are similarities between the behavioural and physiological effects of septal lesions and stress exposure such as increased irritability, resistance to extinction and sympathetic activation (Holdstock, 1967;Chen & Amsel, 1977;Feldon & Gray, 1979;Gray, 1987). Thus, we predicted that septal inactivation might mimic the effect of footshock stress on reinstatement of heroin seeking.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, this area receives connections from the frontal cortex (Gaykerema et al 1991) and sends efferent fibres to different structures, including the hippocampus, amygdala and hypothalamus in rats (Berk & Finkelstein 1981, Meiback & Siege1 1967, Nieuwenhuys et al 1982, Staiger & Nunberger 1991, Dudley et al 1990. T h e septum is involved in the control of emotion-related behaviours such as the activity in a n open field (Lee et al 1988), galvanic skin response, heart rate and blood pressure changes (Covian et al 1964, Holdstock 1967. I t is also reported that septal lesions decrease the level of locomotor activity, accelerate ponderal growth, and increase the concentration of growth hormone and insulin.…”
mentioning
confidence: 99%
“…In collaboration with a number of co-workers the behavioural significance of the septal forebrain has been studied by using electrical stimulation (Holdstock 1967;Bromley & Holdstock 19697, electrophysiological recording (Chalmers & Holdstock 1969;, drug (Chalmers & Holdstock 1969;Holdstock & Ingle 1969) and ablation techniques.…”
mentioning
confidence: 99%